Adult Education in Greece - Koumparoulis, Dimitrios Nikolaou (Mediterranean Journal of Social Sciences, 2011)
The General Secretariat for Adult Education is the executive, public body responsible for adult education andtraining. Its mission is to design, coordinate and support measures which relate to supplementation of basic education and lifelonglearning and training both for the adult workforce of Greece and for persons threatened with social exclusion. Its main fieldsof action relate to basic education supplementation programmes and illiteracy programmes, continuing training courses,measures to combat exclusion from the labour market and Community Initiatives financed by the European Union (EuropeanSocial Fund), social - cultural education courses, continuing training and repeat education measures for the adult workforce. TheGeneral Secretariat for Adult Education has developed a website about life-long learning prospects in Greece. Interested partiescan participate in on-line debate using the site. Moreover, the General Secretariat for Adult Education is the information centrefor the ELECTRA portal for adult education and life-long learning in Europe. Information provided by the centre relates to sixEuropean countries -France, Germany, Greece, Italy, Scotland/Great Britain and Sweden- while its range is expected to beextended soon to cover other E.U. countries.